A new metaphor-less algorithms for the photovoltaic cell parameter estimation - Premkumar M.; Babu T.S.; Umashankar S.; Sowmya R. (Elsevier GmbH, 2023)
Multiobjective optimization; Parameter estimation; Photoelectrochemical cells; Photovoltaic cells; Solar power generation; Cell parameter; Estimated parameter; Local minimums; Optimization algorithms; Pre-mature convergences; Solar cell parameters; Solar photovoltaic system; Solar PVs; Solar cells